Multi-material 3D Models for Temporal Bone Surgical Simulation. (July 2015) - Rose, Austin S.; Kimbell, Julia S.; Webster, Caroline E.; Harrysson, Ola L.A.; Formeister, Eric J.; Buchman, Craig A.
Hypothesis: A simulated, multicolor, multi-material temporal bone model can be created using 3-dimensional (3D) printing that will prove both safe and beneficial in training for actual temporal bone surgical cases. Background: As the process of additive manufacturing, or 3D printing, has become more practical and affordable, a number of applications for the technology in the field of Otolaryngology–Head and Neck Surgery have been considered. One area of promise is temporal bone surgical simulation. Methods: Three-dimensional representations of human temporal bones were created from temporal bone computed tomography (CT) scans using biomedical image processing software. Multi-material models were then printed and dissected in a temporal bone laboratory by attending and resident otolaryngologists. A 5-point Likert scale was used to grade the models for their anatomical accuracy and suitability as a simulation of cadaveric and operative temporal bone drilling. Results: The models produced for this study demonstrate significant anatomic detail and a likeness to human cadaver specimens for drilling and dissection. Conclusion: Simulated temporal bones created by this process have potential benefit in surgical training, preoperative simulation for challenging otologic cases, and the standardized testing of temporal bone surgical skills.